Pendidikan Musik Informal pada Komunitas Jazz di Lampung - Riyan Hidayatullah (Program Studi Pendidikan Musik FBS UNP, 2023)
Purpose: Jazz has grown in popularity recently, and its presence in Lampung has been recognized. This condition is reflected in the emergence of jazz music groups and communities such as the 'Rakata Jazz Community' (RJC) and the 'Kalima Jazz Community' (KJC) (KJC). However, the Lampung jazz community has a pedagogical dimension in addition to its musical and social activities. Several researchers have realized that jazz provides an informal music learning format. This research aims to describe the pedagogical dimensions of jazz in the community and the music landscape of the Lampung jazz community, particularly at RJC and KJC. Method: From 2017 to 2021, I have been actively participating in this ethnographic research as a member of both communities. Digital archives and websites were used to supplement the research data. Result and Discussion: The study's findings indicate that the learning environment and experience are the potentials for the Lampung jazz community to develop its members' knowledge. This potential is demonstrated through performance activities and jam sessions at its regular meetings.